SURVEY KETERAMPILAN TEKNIK DASAR PERMAINAN BOLA BASKET PADA EKSTRAKURIKULER TIM BOLA BASKET PUTRA DI MADRASAH ALIYAH NEGERI 2 KEDIRI TAHUN 2024 - Moh Irfan Cahyono Putra; Wing Prasetya Kurniawan; Puspodari (YLPK Mahardhika, 2024)
This research is motivated by the lack of ability of each individual student in playing basketball in grades X and XI of the extracurricular basketball team of the boys of Madrasah Aliyah Negeri 2 Kediri. This study aims to determine the level of basic basketball technique skills in the extracurricular basketball team of the boys of Madrasah Aliyah Negeri 2 Kediri. This research is a quantitative study. The population in this study was the entire extracurricular basketball team of Madrasah Aliyah Negeri 2 Kediri. The sample of this study was the extracurricular basketball team of the boys of Madrasah Aliyah Negeri 2 Kediri totaling 32 samples. Sampling used purposive sampling technique. The data collection technique used tests and measurements. The results of this study indicate the level of basic basketball skills in extracurricular basketball team boys at Madrasah Aliyah Negeri 2 Kediri, as many as 11 people are categorized as Sufficient in basic dribbling technique skills with a percentage (34%), as many as 12 people are categorized as Sufficient in basic passing technique skills with a percentage (38%), as many as 12 people are categorized as Sufficient in basic shooting technique skills with a percentage (38%).